Gravitational intelligent decision-making model at the fuzzy front end with extrinsic idea integration by the K-means algorithm - VAYVAY, ÖZALP (My University, 2022)
© 2022 by the authors.If the dynamic fuzziness of the Front End (FE) part of New Product Development (NPD) cannot be treated in a timely manner, fuzziness accumulates over other parts of NPD hence NPD can result in costly mistakes. The authors tried to remedy this strategically critical problem by implementing mainstream theoretical/methodological approaches, but they found inherent weaknesses of each. The purpose of this study is to bring an objective and intelligent decision-making model to FE so as to lessen fuzziness of it. Model quantizes ideas based on pillars, and re-clusters them with every new idea addition thanks to combining non-mainstream approaches like K-means, distance-based algorithm with gravitational theory inspiration, an accumulation of idea and an exponential function. Study showed that fuzziness of FE can be lessened by quantizing, and objectively managing. The founded core reasons of fuzziness can guide practitioners and authors for better understanding and coping with fuzziness of FE; moreover, the model can be used by companies. Introducing an objective and intelligent decision-making model working like a human brain to FE is a unique idea that has not been tried ever before.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Kütüphanecilik; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Bilgisayar Bilimleri; Veritabanı ve Veri Yapıları; Matematik; Temel Bilimler; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Library Sciences; Information Systems, Communication and Control Engineering; Control and System Engineering; Computer Sciences; Database and Data Structures; Mathematics; Computer Science; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Sosyal Bilimler (SOC); Bilgisayar Bilimi; Mühendislik; Sosyal Bilimler Genel; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, YAZILIM MÜHENDİSLİĞİ; TELEKOMÜNİKASYON; MATEMATİK, UYGULAMALI; BİLGİ BİLİMİ VE KÜTÜPHANE BİLİMİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Social Sciences (SOC); COMPUTER SCIENCE; ENGINEERING; MATHEMATICS; SOCIAL SCIENCES, GENERAL; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, SOFTWARE ENGINEERING; TELECOMMUNICATIONS; MATHEMATICS, APPLIED; INFORMATION SCIENCE & LIBRARY SCIENCE; Fizik Bilimleri; Yazılım; Modelleme ve Simülasyon; Bilgisayar Ağları ve İletişim; Bilgi Sistemleri ve Yönetimi; Sosyal Bilimler ve Beşeri Bilimler; Control and Systems Engineering; Physical Sciences; Software; Modeling and Simulation; Computer Networks and Communications; Information Systems and Management; Social Sciences & Humanities; Fuzzy Front End (FFE); extrinsic idea integration; K-means; idea selection; intelligent decision-making; decision support; PRODUCT DEVELOPMENT; SUCCESS FACTORS; ARTIFICIAL-INTELLIGENCE; DEVELOPMENT-PROJECTS; INNOVATION TEAMS; EXPERT-SYSTEMS; SOCIAL MEDIA; KANOS MODEL; KNOWLEDGE; MANAGEMENT; Fuzzy Front End (FFE); extrinsic idea integration; K-means; idea selection; intelligent decision-making; decision support